Early Language Development of a Child with Expressive Language Disorder: A Parents’ Narration - Dewi Rosmala; Arini Nurul Hidayati; Fuad Abdullah (J-SHMIC : Journal of English for Academic, 2021)
Mainstream children generally experience typical stages throughout the milestones of their language development, from crying, cooing, babbling, until mature speech. Nevertheless, children with special condition usually have difficulties in getting through each phase of the development, such as those having expressive language disorder. These children usually encounter problems in communicating their needs and ideas verbally or non-verbally. This study attempts to present a story of the first five-year journey of Zaid’s language development, a child with expressive language disorder. Through interview, observation, and documentation, the study informs that Zaid was a late talker and experience difficulties in structuring well-ordered sentences.